TRILOGI PEMBEBASAN ASGHAR ALI ENGINEER: TAFSIR ANTI KEMAPANAN ATAS KETIDAKADILAN - Riady, Fahmi (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2008)
The liberation theology is a theology which puts great ernphasis on fieedom, equality and distributive justice and strongly condemns exploitation of rnan by man, opprcssion and pcrsccution. l'he main character ol'this thcology is its conccrn to thc mustadh'afun (the weak people). Suclr tlrc ology didn't want the status quo rvhich protect the rich people. It's anti-status quo either in religoLrs field or politic one. Such theology play the imporlant role in caring tbr the weak people who his right was under attack. It's also give thc weak a strong ideological weapon facing its tyrant. ln l"act, such theology motivated tlte developing of practical Islam as bargaining position betwecn man and his destiny. It's supposed both are the complement factor between and a nothet' than an antagonislic concePt.